ESTETIKA DALAM KONTEKS PENDIDIKAN SENI - Sunarto Sunarto (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2017)
The core of art is aesthetics, then art education is actually aesthetic education. Aesthetics itself is like a building, it has: roof, wall and hallway (foundation). As a roof, aesthetics give the spirit of art; The aesthetic wall gives themes and contents of art creation, and as aesthetic hall is the goal and background of art creation. Aesthetics are built on ideas, ideas and the purpose of creating works of art According to the results of research on the Art of Public Space in Yogyakarta (2015) shows that the aesthetic building of artwork has moved from the position, from the work to the connoisseur. The move is the latest (Contemporary) art phenomenon, resulting from the thinking of teenagers' paralogism and antihistorianism. This antagonistic, recent development is not anticipated by the learning of Arts Education in public schools.